PENGARUH PEMBERIAN MONOSODIUM GLUTAMAT TERHADAP STRUKTUR MIKROSKOPIS OVARIUM MENCIT (Mus musculus, L.) - Wa Ode Harlis; Sitti Wirdhana Ahmad; Marwati Marwati (University of Halu Oleo, 2015)
ABSTRACTThis study aims to determine the effect of MSG to the microscopic structure of the ovaries of mice. This study was a experimental study using a completely randomized design (CRD). A total of 16 female mice aged 3 month were devided into 4 groups namely P0 (Control), P1 (0,012 mg/gr BB), P2 (0,015 mg/gr BB) and P3 (0,018 mg/gr BB), MSG administration carried out of 14 days. On day 15 the animals were sacrificed and performed organ harvesting ovaries to make histological preparations. Observation were made by observing the histological structure of the ovaries , and count the number of primary follicles, secondary, tertiary, the korpus luteum and follicular atretic. Data were tested with ANOVA, and LSD (α=0,05%). The result showed the existence of structural damage in the form of a gap between the ovarian follicular granulosa cells and ovarium follicle diameter reduced with increasing doses of MSG given. MSG administration also decreases the average number of follicles in all treatment doses, but the mean of the highest drop in the number of follicles present in treatmen P3 that is, the number of primary follicles (2,50), secondary follicles (2,25), tertiary follicles (1,25) and follicular atretic (4,25), while the corpus luteum is not found.Keywords : Monosodium glutamate, Damaged Structure of The Ovaries, Mice (Mus musculus,L)